Absolute Configuration from Different Multifragmentation Pathways in Light‐Induced Coulomb Explosion Imaging. Issue 16 (9th August 2016) - Pitzer, Martin; Kastirke, Gregor; Kunitski, Maksim; Jahnke, Till; Bauer, Tobias; Goihl, Christoph; Trinter, Florian; Schober, Carl; Henrichs, Kevin; Becht, Jasper; Zeller, Stefan; Gassert, Helena; et al.
Abstract: The front cover artwork is provided by the groups of Reinhard Dörner (University of Frankfurt), Robert Berger (University of Marburg) and Jürgen Stohner (Zurich University for Applied Sciences, Wädenswil). The image shows how a single X‐ray photon from a synchrotron source induces the Coulomb Explosion of a prototypical chiral molecule (CHBrClF), allowing to distinguish the enantiomers and determine the absolute configuration. Read the full text of the article at 10.1002/cphc.201501118 . Abstract : "Light‐induced Coulomb explosions can image the absolute configuration of small molecules in the gas phase. It is shown that even partial fragmentation displays the signature of handedness—an important step for the application of Coulomb explosion imaging to larger molecules.…" This and more about the story behind the front cover can be found in the Full Paper at10.1002/cphc.201501118 .